2006
DOI: 10.1121/1.2133436
|View full text |Cite
|
Sign up to set email alerts
|

Perceived speech rate: The effects of articulation rate and speaking style in spontaneous speech

Abstract: In this study, the effect of articulation rate and speaking style on the perceived speech rate is investigated. The articulation rate is measured both in terms of the intended phones, i.e., phones present in the assumed canonical form, and as the number of actual, realized phones per second. The combination of these measures reflects the deletion of phones, which is related to speaking style. The effect of the two rate measures on the perceived speech rate is compared in two listening experiments on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
83
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 15 publications
9
83
4
3
Order By: Relevance
“…We chose this definition rather than the number of syllables per second that were actually produced, because the former measure can be estimated more reliably (as it is based on orthographic rather than phonetic transcriptions). The two measures are highly correlated and research by Koreman (2006) showed that they both contribute to listeners' perception of speech rate. Since speech rate was clearly higher in the components with unscripted than with scripted speech, we orthogonalised the predictors Speech Rate and Component Group by replacing Speech Rate by the residuals of a linear model predicting Speech Rate as a function of Component Group.…”
Section: Resultsmentioning
confidence: 99%
“…We chose this definition rather than the number of syllables per second that were actually produced, because the former measure can be estimated more reliably (as it is based on orthographic rather than phonetic transcriptions). The two measures are highly correlated and research by Koreman (2006) showed that they both contribute to listeners' perception of speech rate. Since speech rate was clearly higher in the components with unscripted than with scripted speech, we orthogonalised the predictors Speech Rate and Component Group by replacing Speech Rate by the residuals of a linear model predicting Speech Rate as a function of Component Group.…”
Section: Resultsmentioning
confidence: 99%
“…For studies that use discourse-length materials (e.g., Anderson-Hsieh & Koehler, 1988;Lin, 2006), calculations of speaking rate are the norm, even though such rates provide no information regarding the frequency, duration, location, or type of pause phenomena. Given that studies by Jacobs et al (1988) and Blau (1990) Additional speech rate measures in the literature include realized phones per second (or the actual consonant and vowel segments in the utterance) and intended phones per second (or the canonical or unreduced form which the utterance could maximally take; Koreman, 2006). For example, a speaker who says wanna for want to deletes the t sound, resulting in one fewer realized phones than intended phones.…”
Section: Speech Rate Definitionsmentioning
confidence: 99%
“…In turn, increased articulatory rate is associated with, for example, decreases in vowel duration, second formant (F2) vowel onsets, and stop closure intervals, as well as with increases in coarticulation, deletion of consonant or vowel segments, and reduction in pitch range and pitch resets (e.g., Guion, Flege, Akahane-Yamada, & Pruitt, 2000;Koreman, 2006;Lindblom, Sussman, & Agwuele, 2009). As segment durations decrease (relative to some slower rate), speakers may undershoot or hypoarticulate segments given that they will have less time to reach the intended motor targets (e.g., Byrd & Tan, 1996;Lindblom et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also the variable on which listeners mainly rely to perceptually evaluate the pace at which an utterance is produced (Koreman, 2006;Lane & Grosjean, 1973). In fact, AR refers to the number of units (e.g.…”
Section: Introductionmentioning
confidence: 99%